The Arabidopsis B-BOX Protein BBX25 Interacts with HY5, Negatively Regulating BBX22 Expression to Suppress Seedling Photomorphogenesis - Gangappa, Sreeramaiah N. (2013)
ELONGATED HYPOCOTYL5 (HY5) is a basic domain/leucine zipper (bZIP) transcription factor, central for the regulation of seedling photomorphogenesis. Here, we identified a B-BOX (BBX)–containing protein, BBX25/SALT TOLERANCE HOMOLOG, as an interacting partner of HY5, which has been previously found to physically interact with CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1). BBX25 physically interacts with HY5 both in vitro and in vivo. By physiological and genetic approaches, we showed that BBX25 is a negative regulator of seedling photomorphogenesis. BBX25 and its homolog BBX24 regulate deetiolation processes and hypocotyl shade avoidance response in an additive manner. Moreover, genetic relationships of bbx25 and bbx24 with hy5 and cop1 revealed that BBX25 and BBX24 additively enhance COP1 and suppress HY5 functions. BBX25 accumulates in a light-dependent manner and undergoes COP1-mediated degradation in dark and light conditions. Furthermore, a protoplast cotransfection assay showed that BBX24 and BBX25 repress BBX22 expression by interfering with HY5 transcriptional activity. As HY5 binds to the BBX22 promoter and promotes its expression, our results identify a direct mechanism through which the expression of BBX22 is regulated. We suggest that BBX25 and BBX24 function as transcriptional corepressors, probably by forming inactive heterodimers with HY5, downregulating BBX22 expression for the fine-tuning of light-mediated seedling development.